2014
DOI: 10.4137/rpo.s12755
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Conceptions of Stuttering

Abstract: The conceptions about stuttering vary amongst cultures. Culturally specific findings regarding stuttering help in understanding the peoples' views and conceptions about stuttering and devising awareness and counselling strategies. A total of 132 passengers on the Coromandal Express from Chennai to Howrah participated in this study. All of them belonged to the upper middle socioeconomic class. Preliminary Stuttering Conception Questionnaire (PSCQ) was used to understand their conceptions of stuttering. 23% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Interestingly, Table 2 shows that 90% of the respondents in our study indicated that they considered stuttering to be a sensitive matter and they avoided talking about it with those who stutter. This is consistent with some African beliefs that stuttering is infectious (McKenzie, 1992 ; Rout et al, 2014 ) and discussing it can result in infection. There is somewhat of a contradiction because all the respondents indicated that they communicated with the PWS the same way that they do with those who do not stutter.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, Table 2 shows that 90% of the respondents in our study indicated that they considered stuttering to be a sensitive matter and they avoided talking about it with those who stutter. This is consistent with some African beliefs that stuttering is infectious (McKenzie, 1992 ; Rout et al, 2014 ) and discussing it can result in infection. There is somewhat of a contradiction because all the respondents indicated that they communicated with the PWS the same way that they do with those who do not stutter.…”
Section: Resultssupporting
confidence: 88%
“…Results of the survey show low levels of understanding of stuttering (75%). A study conducted in India by Rout et al ( 2014 ) also found that the participants in their study knew little about stuttering, but their perceptions about the cause and management were mostly fallacious. In our study, 60% of our respondents indicated that they hardly understood when speaking with someone who stutters and knew little about stuttering.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation